Benefits of EEG theta rhythm analyses for athletic training and competitive progress systems - Karatygin, N. A.; Korobeinikova, I. I.; Venerina, Y. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze benefits of the EEG theta rhythm tests for competitive performance rating purposes in some sports disciplines, with the EEG theta-activity rates applicable as the competitive progress biomarkers.